PreImplantation factor promotes neuroprotection by targeting microRNA let-7 - Mueller, Martin (National Academy of Sciences, 2014)
Dysfunction and loss of neurons are the major characteristics of CNS disorders that include stroke, multiple sclerosis, and Alzheimer’s disease. Activation of the Toll-like receptor 7 by extracellular microRNA let-7, a highly expressed microRNA in the CNS, induces neuronal cell death. Let-7 released from injured neurons and immune cells acts on neighboring cells, exacerbating CNS damage. Here we show that a synthetic peptide analogous to the mammalian PreImplantation factor (PIF) secreted by developing embryos and which is present in the maternal circulation during pregnancy inhibits the biogenesis of let-7 in both neuronal and immune cells of the mouse. The synthetic peptide, sPIF, destabilizes KH-type splicing regulatory protein (KSRP), a key microRNA-processing protein, in a Toll-like receptor 4 (TLR4)–dependent manner, leading to decreased production of let-7. Furthermore, s.c. administration of sPIF into neonatal rats following hypoxic-ischemic brain injury robustly rescued cortical volume and number of neurons and decreased the detrimental glial response, as is consistent with diminished levels of KSRP and let-7 in sPIF-treated brains. Our results reveal a previously unexpected mechanism of action of PIF and underscore the potential clinical utility of sPIF in treating hypoxic-ischemic brain damage. The newly identified PIF/TLR4/KSRP/let-7 regulatory axis also may operate during embryo implantation and development.